Health and migration in the context of a changing climate: a systematic literature assessment. (30th September 2020) - Schwerdtle, Patricia Nayna; McMichael, Celia; Mank, Isabel; Sauerborn, Rainer; Danquah, Ina; Bowen, Kathryn J
Abstract: Background. Climate change and climate variability interact with political, economic, social, demographic, and other environmental drivers to change the scale and patterns of human migration 5 . In the context of accelerating climate change and breaches to other planetary boundaries, there is an urgent need to better understand how migrant health can be protected and promoted in the context of a changing climate to manage safe and orderly migration 6 . While research has focused on the separate dyads of (i) climate change and migration and (ii) climate change and health, limited consideration has been given to the nexus between climate change, migration, and health. This assessment synthesizes research that has investigated this relationship since 1990. Methods. Following an a priori protocol and with the assistance of a subject librarian, systematic searches were conducted in four academic databases (PubMed, Scopus, Ovid Medline, and Global Health) and Google Scholar for empirical studies investigating migration and health in the context of climate change with any study design between 1990 and 2018. The search results underwent a two-stage screening process and the eligible studies were subjected to quality appraisal using a mixed methods appraisal tool. Data extraction and a meta-synthesis followed producing outputs deemed most useful for policy, practice, and further research. Findings. The registered protocol and search strategy revealed 1904 studies of which 180 were screened in full- text and 50 were included in the meta-synthesis. Overall, the methodological and reporting quality of the included studies was high. This assessment produced five main findings: (1) there is a paucity of empirical research investigating the climate-health-migration nexus; (2) the relationships between migration and health in the context of climate change are strongly heterogeneous and global findings are unlikely to emerge; (3) studies have examined diverse health issues associated with migration in the context of climate change including changing patterns of infectious disease, non-communicable disease, psychosocial conditions, and access to health care; (4) food and water security are important mediators between climate change, human mobility and health outcomes; (5) there is no consistent approach to integrating climate data in studies exploring migration and health in the context of climate change. Conclusions. Although migrant health and climate-related health risks are significant population health concerns, there has been limited consideration of the complex connections between climate change, migration, and health. This assessment indicates that there are potentially important intersections between climate-health- migration and that further research is required to better understand this nexus. To date and based on this assessment, it seems important that research and policy related to migration also consider the links between climate change and health and that migration is considered a determinant of health in climate change and health research. Given the diverse mobility patterns that arise in the context of climate change, responsive approaches are required that address the vulnerabilities of communities at risk of, or involved in forced migration, whilst supporting the adaptive potential of mobility responses. There is a need to develop policies that are responsive enough to protect health and health determinants especially food and water security regardless of the climate scenario. The degree to which climate data are meaningfully integrated into research exploring migration and health in the context of a changing climate warrants further consideration and analysis, to maintain quality in this emerging field of nexus research. Health systems that are migrant inclusive and climate-resilient have the potential to mitigate the worst health impacts of climate-related migration.